Application of GIS technology in the construction of landscape maps (Journal of Geography and Environmental Management, 2016)
The paper set out the practical use of GIS technology in the preparation of landscape maps. The author has shown in the examples of the implementation of the process of work with immitirovaniem management operations before the computer systems. For that, the software ArcGIS 9.3 and predstvleny composed landscape map Zhambyl district of Almaty region 1:100 000 scale.
Keywords: GIS technologies; landscapes